PERTIMBANGAN HAKIM DALAM PERKARA PERBUATAN MELAWAN HUKUM PELELANGAN OBJEK SENGKETA YANG CACAT HUKUM (PUTUSAN MAHKAMAH AGUNG NOMOR 2893 K/PDT/2021) - Yeremiarim, Omega Kharisma; Djajaputra, Gunawan (UNES Law Review, 2023)
Auction is a method of offering goods by verbally mentioning the price from the highest to the lowest. This writing aims to find out the material law that should be stipulated in this case and to find out the basis for the judge's considerations in deciding case Number 2893 K/Pdt/2021. This research approach is a normative juridical approach by discussing the doctrine or legal principles contained in statutory regulations. The results of this study are that the court can cancel the cancellation of auction for the execution of the Mortgage. Cancellations can only be canceled before the auction is held, this is by the provisions in Article 24 of the Minister of Finance Regulation No.106/PMK.06/2013 which states that the auction can be canceled by a court decision before the auction is held. Cancellations of auctions submitted after the auction has occurred cannot be carried out, this is in accordance with the provisions in Article 3 of Minister of Finance Regulation No.106/PMK.06/2013 which reads that auctions that have been carried out in accordance with applicable regulations cannot be cancelled.